HUBUNGAN ASUPAN ZAT GIZI MAKRO DAN IMT DENGAN SINDROM METABOLIK PADA PEGAWAI PERUSAHAAN TAMBANG - Niken Meldy Puryanti; Ibnu Malkan Bakhrul Ilmi; Taufik Maryusman (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2021)
Background: Most of the company's employees are administrative tasks. The work environment can affect the nutritional status and employee intake. Poor health conditions can affect employee productivity. One of the health problems is the metabolic syndrome in Jakarta executive employees is quite large to reach 21.58%. High nutrient intake and obesity are among the factors triggering the accumulation of the disease into metabolic syndrome. This study aims to analyse relationship macronutrient and nutritional status (BMI) with metabolic syndrome in employees of Mining Company. Method: Cross-sectional studi with a purposive sampling involving 62 employees. Data were collected from food recall 24 hours interview via chat and medical check-up. Result: The result is the incidence of metabolic syndrome criteria were 4 employees. There were not relationship between carbohydrate (p=0,404), protein (p=0,404), fat (p=285), and nutritional status (BMI) (p=0,426) with metabolic syndrome. Discussion: There were not relationship between macronutrient (carbohydrate, fat, and protein) and nutrition status (BMI) with metabolic syndrome.